Yield and quality of sugar snap pea in the Ebro Valley: sowing date and seed density (Scientia Agricola, 2012)
Sugar snap pea (Pisum sativum L. var. macrocarpon Ser.) is an edible-podded sweet pea that is being considered as a new totally mechanized crop to supply raw material to the agri-food industry of the Ebro Valley (Northern Spain). It is of great interest from an agronomic and commercial standpoint but neither its agronomic behaviour nor its adaptation to the area are known. The objective of this study was to determine the effect of sowing date and seed density on the growth and yield of the sugar snap pea at industrial scale. Six randomized blocks experiments with four replicates were conducted on irrigated land in Villafranca (Navarra, Spain) in 1998, 1999, and 2000. Three experiments for testing sowing dates (Mar., Apr., and May) and another three for seed densities (from 75 to 150 plants m-2) were performed. Phenological development, thermal integral and qualitative and quantitative yield controls were performed. Sugar snap pea required 960 ºC d-1 (Tb = 3 ºC) from sowing to harvest. The early sowings gave more biomass, but yield was similar. However, Harvest Index and crop morphology varied. The sowing densities had similar yields sowing that sugar snap pea has a bigger adaptation availability. Sugar snap peas can be satisfactorily cultivated at industrial scale in the zone with sowings between Mar. and May and with seeding densities between 75 and 150 plants m-2.